2020
DOI: 10.1007/s42452-020-3123-3
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and bioaccumulation of trace metals from industrial effluent to locally grown vegetables and assessment of human health risk in Bangladesh

Abstract: In this study, we evaluated the level of trace metals in the soil of heavily loaded tannery and battery industry area on the bank of the Buriganga River, Dhaka, Bangladesh in order to investigate their translocation to the locally grown vegetables and potential health risk of the local consumers. Concentrations of various metals in agricultural soil and in a number of vegetables such as; Red amaranth (Amaranthus cruentus), Spinach (Spanacia oleracea), Jute leaf (Corchorus capsularies), Bottle Gourd (Lagenaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 48 publications
0
16
2
Order By: Relevance
“…Several researchers analyzed soil from area adjacent to river and compared with uncontaminated soil and found that these soils contain higher concentrations of heavy metals [ 12 , 182 ]. Crop grown in contaminated soil having irrigated with contaminated water accumulate higher concentrations of metals compared to uncontaminated soil and water [ 203 , 204 , 205 ]. Most of the researchers collected soil, water and crops from the agricultural land close to contaminated river and showed the toxicity level of contamination.…”
Section: Changes Of Heavy Metals Concentration In Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers analyzed soil from area adjacent to river and compared with uncontaminated soil and found that these soils contain higher concentrations of heavy metals [ 12 , 182 ]. Crop grown in contaminated soil having irrigated with contaminated water accumulate higher concentrations of metals compared to uncontaminated soil and water [ 203 , 204 , 205 ]. Most of the researchers collected soil, water and crops from the agricultural land close to contaminated river and showed the toxicity level of contamination.…”
Section: Changes Of Heavy Metals Concentration In Soilmentioning
confidence: 99%
“…Metals enter into food chain through the accumulation into foodstuffs and finally come to human. Continuous consumption of the contaminated foods will build up higher concentrations gradient of the toxic metals into human body which will causes non carcinogenic and carcinogenic health hazards [ 205 ].…”
Section: Bioaccumulation Of Toxic Metals Into Foodstuff and Human Heamentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the presence of high number of leather industries in the vicinity. These industries use chrome salts for leather processing and dump their waste mostly without any treatment in the nearby Buriganga River (Md Didarul Islam et al, 2020). Thus, it is not recommended that to drink much milk from those locations where samples were collected (nearby) in terms of highly chromium contamination and government should set up a strict guideline for tannery waste disposal system and it should be regularly monitored.…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…In a study performed by Islam et al (2020) near Buriganga River in Bangladesh, a variety of vegetables are collected, namely red amaranth, spinach, jet, squash, green mustard and water spinach from six different locations. They have foundthat the bioaccumulation factorhas recorded values greater than one and for all heavy elements, namely chromium, nickel, copper, zinc, cadmium and lead in all plants.…”
Section: Introductionmentioning
confidence: 99%